ELECTROCHEMICAL ANALYSIS OF ZINECARD IN PHARMACEUTICAL AND BIOLOGICAL SAMPLES - Chennupalle Nageswara Reddy; Puthalapattu Reddy Prasad; Neelam Yugandhar Sreedhar (Indonesian Journal of Pharmacy, 2012)
Zinecard is used to prevent a toxic effect to heart caused by certain medicines that are used to treat cancer.  Zinecard  is also  used  to  treat  tissue  damage  caused  by  the  leakage  of certain  medicines  that  are  used  to  treat  cancer.  Differential pulse  polarographic  method   developed  for  the  quantitative determination  of  zinecard  gives  a  peak  at  -0.32  V  at  DME. From  the  structural  point  of  view  zinecard  contains  a  >C=Omoiety  which  can  be  electrochemically  reduced  at  universal buffer  (pH  4.0).  Millicoulometric  experiment  is  performed successfully  in  estimating  the  number  of  electrons  and  proton to  understand  reduction  mechanism.  The  differential  pulse polarographic peak was adequately well-resolved, reproducible and  linear  dependent  with  the  zinecard  concentration.  For quantification  the  calibration  plot   for  zinecard  concentrations ranging  between  1.0×10-5mol  dm-3 to  1.0×10-8mol  dm-3 at pH  4.0  was  selected.  The  proposed  differential  pulse polarographic  method  was  successfully  applied  to  the determination  of  zinecard  in  pharmaceutical  formulations  and urine samples.Key words:  Zinecard,    DPP,    pharmaceutical    formulations    and urine samples.